¿Qué posibilidad de discusión y acuerdo hay para Kant respecto de diversos juicios de gusto? - Pomposini, Antonio (2017)
This paper examines the importance that judgements of taste have within Kant’s Critique of Judgement. It claims that looking for de facto agreements about judgements of taste is a mistake and that disagreements, instead, are desirable. Following Kant in the antinomy of taste, judgments of taste are not based on determined concepts, but rather on an undetermined one. Since the concept is not determined one cannot exhibit it in a sensible intuition or make direct reference to it. It is argued that universal agreement does not seek de facto agreement, but rather the discovery of a common sense in which one discovers that others can feel the same as one does with respect to a given representation. This undetermined concept becomes a “regulative ideal”, unobtainable in so far as one cannot determine it, but to which one must aim in order to perfect one’s taste. It is in the sphere of discussion and disagreement that one confronts one’s judgements of taste.